2015
DOI: 10.1016/j.gaitpost.2014.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Non-uniform in vivo deformations of the human Achilles tendon during walking

Abstract: The free Achilles tendon (AT) consists of distinct fascicles arising from each of the triceps surae muscles that may give rise to non-uniform behavior during functional tasks such as walking. Here, we estimated in vivo deformations of the human AT during walking using simultaneous ultrasound and motion capture measurements. Ten subjects walked at three speeds (0.75, 1.00, and 1.25 m/s) on a force-measuring treadmill. A custom orthotic secured a linear array transducer in two locations: 1) the distal lateral ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
133
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 112 publications
(146 citation statements)
references
References 32 publications
11
133
0
Order By: Relevance
“…Haraldsson et al (12) suggested that sliding between AT fascicles may allow them to behave as functionally independent structures. Consistent with these observations, we recently discovered in young adults that tendon fascicles presumably arising from the medial gastrocnemius undergo ϳ30% greater peak elongation than those from the soleus during walking (9). These depth-dependent differences became larger with faster walking speed.…”
supporting
confidence: 77%
See 1 more Smart Citation
“…Haraldsson et al (12) suggested that sliding between AT fascicles may allow them to behave as functionally independent structures. Consistent with these observations, we recently discovered in young adults that tendon fascicles presumably arising from the medial gastrocnemius undergo ϳ30% greater peak elongation than those from the soleus during walking (9). These depth-dependent differences became larger with faster walking speed.…”
supporting
confidence: 77%
“…Based on in vivo ultrasound measurements, we recently proposed that sliding between AT fascicle bundles may allow for relatively independent muscle fiber behavior in the triceps surae muscles. This in turn may promote the muscle-tendon coordination necessary for effective force or power generation during pushoff (9). Age-related changes in AT behavior may compromise sliding between adjacent tendon fascicles (36) and thereby alter the coordination of gastrocnemius and soleus muscle actions in walking.…”
mentioning
confidence: 99%
“…The influence of this design on muscle fascicle and tendon energetics remains an area of future research. We note here, however, that recent in vivo studies on non-uniform Achilles tendon deformation have observed that tendon fascicles arising from the SO and gastrocnemius may function as independent structures during walking [67,68].…”
mentioning
confidence: 55%
“…This highlights the complexity of loading on the Achilles tendon with contributions from three independent muscles, which have been suggested to constitute mechanically separate tendon compartments within the Achilles (Bojsen-Moller and Magnusson, 2015). Indeed, ultrasound speckle tracking methods have shown greater elongation within the deeper region of the Achilles tendon compared with the superficial layer during loading (Arndt et al, 2012;Franz et al, 2015;Slane and Thelen, 2015). This may suggest the presence of inter-fascicle sliding and a relative independence of gastrocnemius and soleus tendon components functioning within the Achilles tendon.…”
Section: Discussionmentioning
confidence: 92%